A STUDY ON THE IMPACT ON THE RECOGNITION OF INTANGIBLE ASSETS UPON ADOPTION OF INTERNATIONAL ACCOUNTING STANDARDS IN BRAZILIAN COMPANIES LISTED ON THE BM&FBOVESPA - Silva Filho, Lucivaldo Lourenço (2014)
According to CPC 04 (R1) intangible assets are identifiable non-monetary asset without physical substance. The aim of this study was to verify if after the adoption of international accounting standards was no change in the recognition of intangible assets in the balance sheet of the companies listed on BM&FBovespa, checking if the behavior of the recognition of intangible occurred evenly between existing economic sectors. For this study, we divided the intangible assets into two groups: those identifiable intangibles and unidentifiable intangible (goodwill). The sample consisted of 10 sectors represented in 213 companies listed on the BM&FBovespa, in a period of 6 years from 2005 to 2007 (before the adoption of IAS / IFRS) and 2009-2011 (after adoption of IAS / IFRS). The results indicated that there was greater recognition of identifiable intangible in all sectors studied following the adoption of IAS / IFRS, with emphasis on the construction industry and transport had increased recognition of 44,75%. With respect to goodwill, only the sector of industrial goods increased by statistically significant recognition. What about the total intangible assets 7 of 10 sectors studied showed increased recognition. It is recommended for further studies to investigate whether a relationship exists due to the accounting regulation of these sectors. The sectors that showed no increase in the recognition of intangible totals were the telephone, oil, gas and biofuels, and information technology. From these results, it appears that the changes introduced in the rulings of the Comitê de Pronunciamentos Contábeis and the Conselho Federal de Contabilidade effectively contributed to the increased recognition of intangible assets in the financial statements of listed companies in all sectors of BM&FBovespa.